Preparation of educational technology like na interdisciplinar y booklet on alcoholic fermentation to improve learning in Chemistry Teaching (Research, Society and Development, 2024)
Educational technologies that facilite the teaching-learning process in the area of chemistry are importante tools that contribute to the significant construction of knowledge. Didatic materials that combine theory and pratice help to understand the content. The main objective work is develop na educational, interdisciplinar booklet, wich integrates the disciplines of Chemistry, Microbiology and Biochemistry, addressing the topic of alcoholic fermentation. To prepare the booklet, initially, a literature review was carried out on topic of alcoholic fermentation, and, secondly, pratices were selected that contibuted to addressing the interdisciplinarity between Chemical, Microbiolgical and Biochemical knowledge. The booklet was presented to 41 students at federal school, in Caucaia showing good acceptance by the students. The booklet can be used a additional material, in the Chemistry subject, for high school students, to facilite the learning of alcoholic fermentation content.